University Calculus: Early Transcendentals (3rd Edition)

Published by Pearson
ISBN 10: 0321999584
ISBN 13: 978-0-32199-958-0

Chapter 7 - Practice Exercises - Page 421: 31



Work Step by Step

Given: $e^{-x-y-2}=(e^{-y})(e^{-x-2})$ Re-arrange as: $\dfrac{dy}{dx}=(e^{-y})(e^{-x-2})$ Separate the differentials and integrate. $\int e^y dy=\int \dfrac{e^{-x}}{e^2}dx$ This implies that $e^2e^y=-e^{-x}+ce^2$ Applying the initial conditions $y(0)=0$, we get Thus, $e^{0}=-\dfrac{e^{-0}}{e^2}+c \implies c=1+\dfrac{1}{e^2}$ Hence, $e^y=-\dfrac{e^{-x}}{e^2}+1+\dfrac{1}{e^2}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.